Consumer's perceptions of advertising in emerging markets. - Lim, Hui Ying. (2008)
The research aims to provide an insight into the individual emerging market structures and the perceptions towards advertising. Emerging markets are experiencing new focus of advertising. This calls for a need for international marketers to focus on ways to communicate with the growth markets of the future.